The Use of Dugem (game world) Application in Overcoming Learning Loss in Sociology Learning - Anna Rusmiyati (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
The existence of games does not always have a negative impact, when a teacher is able to create innovation and modify a game, what emerges is innovative, creative, and solutive learning. From the application of the Dugem application using Appgeyser, there are several things that we can say here, including, (1) This game is able to restore the enthusiasm and enthusiasm of students learning in Sociology material so that it can minimize the occurrence of learning loss in the implementation of limited PTM, (2) Dugem is able to stimulate students to remember and relearn Sociology material that has been learned, (3) Able to increase literacy, collaboration, and communication between students, (4) Optimizing the use of android smartphones in learning, (5) With the Dugem application can motivate teachers to use information technology and make learning media. So beautiful and happy even when face-to-face learning is still limited, where teachers and students are able to present fun learning so that the feared learning loss can be handled. Our role as a teacher must be maximized, so strategies, tricks, and packaging learning methods that are fun and not boring are needed to recreate active, creative and innovative learning. One of them is by using the Dugem application in the Sociology subject. The hope is that students will more easily remember and understand the material delivered by the teacher, as well as to help stimulate the brain and senses, as well as train emotional intelligence and social intelligence. When seeing students understand the material we convey, there is a sense of satisfaction for a teacher who has succeeded in presenting learning according to their expectations.